Market Analysis for Global Tourism Growth: Analisis Pasar untuk Pertumbuhan Pariwisata Global - Murtiningrum, Susi; Fitriyah, Hadiah (Indonesian Journal of Innovation Studies, 2024)
This qualitative study explores market analysis to enhance tourism promotion and development in Mojokerto Regency, focusing on Coban Canggu, Ubalan Waterpark, and Hot Spring Tourism. Through observations, interviews, and documentation, factors influencing tourist visits were analyzed using the marketing mix elements (product, price, place, promotion, people, process). Findings indicate the importance of attractive attractions, affordability, strategic location, effective promotion, quality service, and efficient management processes. Recommendations include facility improvements, strategic promotions, and community partnerships. This research provides insights for policymakers and stakeholders to improve tourist experiences and economic benefits in Mojokerto Regency. Highlights: Qualitative Analysis: Understanding tourist visit factors. Marketing Mix: Analyzing key elements for effective strategies. Recommendations: Upgrade facilities, strategic promotions, community partnerships. Keywords: Tourism, Market Analysis, Mojokerto Regency, Promotion, Development